2015
DOI: 10.1039/c5ra16515f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a thrombin inhibitor grafted polyethersulfone blending membrane with improved antithrombotic property

Abstract: A thrombin inhibitor grafted polyethersulfone membrane with improved antithrombotic property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 46 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…These membranes showed low hemolysis (0.40 ± 0.07%), prolonged blood coagulation time (activated partial thromboplastin time = 78.5 ± 1.0 s, prothrombin time = 19.1 ± 0.1 s, thrombin time = 25.2 ± 0.1 s, and fibrinogen time = 22.2 ± 1.0 s), and low level of activated terminal complement complex (5.9 ± 1.5 ng/mL). These values of hemolysis, blood coagulation times, and complement activation are better than the literature-reported values, [7][8][9][10][11]15,18,19 which indicates that the cGTP HFMs are suitable for the blood-contact applications, e.g., BAK application. The improved compatibility of cGTP HFMs with the human blood can be attributed to the presence of the biocompatible entities (GO, TPGS, and ECMs) in the surface-functionalized (cGTP) HFMs as discussed in the literature reports.…”
Section: Resultsmentioning
confidence: 82%
“…These membranes showed low hemolysis (0.40 ± 0.07%), prolonged blood coagulation time (activated partial thromboplastin time = 78.5 ± 1.0 s, prothrombin time = 19.1 ± 0.1 s, thrombin time = 25.2 ± 0.1 s, and fibrinogen time = 22.2 ± 1.0 s), and low level of activated terminal complement complex (5.9 ± 1.5 ng/mL). These values of hemolysis, blood coagulation times, and complement activation are better than the literature-reported values, [7][8][9][10][11]15,18,19 which indicates that the cGTP HFMs are suitable for the blood-contact applications, e.g., BAK application. The improved compatibility of cGTP HFMs with the human blood can be attributed to the presence of the biocompatible entities (GO, TPGS, and ECMs) in the surface-functionalized (cGTP) HFMs as discussed in the literature reports.…”
Section: Resultsmentioning
confidence: 82%
“…As shown in Figure , APTT, PT, TT, and FT is the highest for PT‐NZ HFMs, among all the HFMs including the commercial F60S HFMs considered for the study. As seen from the Table , the clotting time (TT, APTT, PT, and FT) of PT‐NZ HFMs is higher than that of the majority membranes reported in literature except PT value of citric acid‐grafted‐polyurethane‐blended polyethersulfone (PES) membranes and APTT value of functionalized MWCNT‐based sulphonated‐PES membranes . The incorporation of TPGS results in prolonged time values for PT and PT‐NZ HFMs.…”
Section: Resultsmentioning
confidence: 87%
“…PES‐COOH was prepared by two‐step reactions: acetylation followed by oxidation . Initially, 7‐g PES were dried using an oven set with a temperature of 110°C for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the ratio of PES membrane (M‐1) was 20% w /w in respect to the solvent (NMP). On the basis of previous studies, it was found that the best blending ratio to the PES is 1: l; therefore, PES‐ABS and PES‐AMBS were blended to PES in a ratio of 1:1 as shown in Table (M‐2 and M‐6), respectively. To enhance the antibacterial properties, ZnO nanoparticles were added to the membrane in a ratio of 2%, 3%, and 5% w /w in which the nanoparticles were suspended first in NMP and sonicated for 30 minutes at 60°C in a water bath in order to suspend the ZnO nanoparticles.…”
Section: Methodsmentioning
confidence: 99%